Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages LABOUR'S FIRST YEAR [Picture] "We are not only a Government, We look like a Government." HERBERT MORRISON 1945-46 SIXPENCE 15X/2/98/21